Magnetic Resonance Spectroscopy 2012
DOI: 10.5772/32340
|View full text |Cite
|
Sign up to set email alerts
|

MR Spectroscopy in Multiple Sclerosis - A New Piece of the Puzzle or Just a New Puzzle

Abstract: Systems do not exist in Nature but only in man's minds. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 112 publications
1
1
0
Order By: Relevance
“…At the same time, the Cho peak showed no significant changes 11 . Similarly, a study presented by Aboul-Enein reported decreases in NAA, Cho, and Cr peaks in parallel with increasing disease severity 10 . In our study, the most significant change was observed in the NAA peak.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…At the same time, the Cho peak showed no significant changes 11 . Similarly, a study presented by Aboul-Enein reported decreases in NAA, Cho, and Cr peaks in parallel with increasing disease severity 10 . In our study, the most significant change was observed in the NAA peak.…”
Section: Resultssupporting
confidence: 54%
“…Furthermore, N-acetylaspartate (NAA) peak decreases when an orientation from RRMS to SPMS occurs during the course of the disease. NAA peaks were shortened when RRMS switched to SPMS during the MS course 10,11 . Pan et al determined MRS metabolic values in RRMS, SPMS, and PPMS groups and calculated metabolic changes by statistical methods 12 .…”
Section: Introductionmentioning
confidence: 99%